Problematika Penegakan Hukum Pertambangan Timah Ilegal dalam Mewujudkan Restorative Justice: Studi di Kepolisian Resor Bangka - Rio Armanda Agustian; Reko Dwi Salfutra; Rahmat Robuwan (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2021)
Law enforcement against criminal acts without a permit (illegal mining) must be carried out for the sake of social justice for all Indonesian people. The Bangka Resort Police, as one of the institutions of the Indonesian National Police, has duties and obligations in realizing ideal conditions both in law enforcement efforts and other persuasive efforts, must be fast and responsive in tackling illegal mining. In this regard, this research aims to examine law enforcement problems of illegal tin mining in realizing restorative justice with the locus of study, namely the Bangka Resort Police. The formulation of the problem studied in this research is as follows. First, what are the legal issues to realizing restorative justice in the enforcement of illegal tin mining crimes by the Bangka Resort Police? Second, how are the efforts of the Bangka Resort Police to overcome the obstacles in law enforcement against the criminal act of illegal tin mining? The legal problems that occur involve various dimensions, namely the dimensions of competence, personnel commitment, supporting facilities and infrastructure, and issues from the social environment of the community. Multiple efforts have been carried out by the Bangka Resort Police in the internal aspect and implementing progressive actions as a form of dedication by law enforcement officials.